2019
DOI: 10.2967/jnumed.119.226472
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Tumor Control in 90Y Radioembolization by Logit Models with PET/CT-Based Dose Metrics

Abstract: The aim of this work was to develop models for tumor control probability (TCP) in radioembolization with 90 Y PET/CT-derived radiobiologic dose metrics. Methods: Patients with primary liver cancer or liver metastases who underwent radioembolization with glass microspheres were imaged with 90 Y PET/CT for voxel-level dosimetry to determine lesion absorbed dose (AD) metrics, biological effective dose (BED) metrics, equivalent uniform dose, and equivalent uniform BED for 28 treatments (89 lesions). The lesion dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(80 citation statements)
references
References 33 publications
6
74
0
Order By: Relevance
“…Recent studies, by our group and others have reported on the association between post-therapy 90 Y imaging derived lesion absorbed dose and outcome (response, survival) in patients treated with 90 Y radioembolization for primary and metastatic liver cancer [14][15][16][17][18]. However, to our knowledge, our current study is the rst investigation to combine lesion radiomics features with absorbed dose metrics to predict outcome.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…Recent studies, by our group and others have reported on the association between post-therapy 90 Y imaging derived lesion absorbed dose and outcome (response, survival) in patients treated with 90 Y radioembolization for primary and metastatic liver cancer [14][15][16][17][18]. However, to our knowledge, our current study is the rst investigation to combine lesion radiomics features with absorbed dose metrics to predict outcome.…”
Section: Introductionmentioning
confidence: 89%
“…Images were acquired on a Siemens Biograph mCT PET/CT within a couple of hours of the RE procedure (prior to discharge) with an acquisition time of ~30 minutes to cover the entire liver and partial lung. PET reconstruction parameters were selected based on phantom studies considering both activity recovery and noise: 1 iteration, 21 subsets of 3D OS-EM with time-of-ight and resolution recovery and a 5 mm Gaussian post-lter [18]. The PET matrix size was 200×200 with a pixel size 4.07×4.07 mm and a slice thickness of 3 mm.…”
Section: Y Pet/ct Imaging and Dosimetrymentioning
confidence: 99%
See 2 more Smart Citations
“…features both achieve high accuracy in discriminating patient response to radioembolization (RE) with 90 Y resin microspheres in terms of serologic response and survival status [13]. Recent studies, by our group and others have reported on the association between post-therapy 90 Y imaging derived lesion absorbed dose and outcome (response, survival) in patients treated with 90 Y radioembolization for primary and metastatic liver cancer [14][15][16][17][18]. However, to our knowledge, our current study is the first investigation to combine lesion radiomics features with absorbed dose metrics to predict outcome.…”
Section: Gensure Et Al Found Tumor Contrast-enhanced Ct Based Textonmentioning
confidence: 99%